Analisis Faktor-faktor yang Memengaruhi Harga Beras di Indonesia pada Januari – November 2024 - Raihan, Muhammad; Ekowati, Titik; Setiadi, Agus (Universitas Galuh, 2026)
Rice prices play a crucial role in Indonesia’s economic stability and public welfare, as rice remains the country’s primary staple food commodity. Price fluctuations are influenced by various internal factors, such as production and stock levels, as well as external factors like exchange rates and import volume. This study aims to analyze the factors affecting rice prices in Indonesia during the period of January to November 2024. The data used are monthly time-series secondary data obtained from the Badan Pangan Nasional, Badan Pusat Statistik, and Bank Indonesia. The analytical method used is multiple linear regression with six independent variables: production volume, demand, import volume, exchange rate, 2023 rice price, and national rice stock, and one dependent variable, the 2024 rice price. The results show that all independent variables simultaneously have a significant effect on rice prices, with an F-value of 9.042 and a significance level of 0.026 (<0.05). Partially, production volume and national rice stock have a significant influence on rice prices, while other variables show no significant effect. The adjusted R² value of 0.842 indicates that 84.2% of the variation in rice prices is explained by the model, with the remainder influenced by external factors. These findings confirm that domestic factors, particularly production and national rice stock, are the main determinants of rice price stability in Indonesia.